Activities of Tembusu Plants (Cyrtophyllum fragrans (Roxb.) DC.) As Medicinal Plants; Literature Review Article - Bunga Anggreini Sari; Eddy Mart Salim; Irsan Saleh (Universitas Hang Tuah, 2023)
Tembusu (Cyrtophyllum fragrans (Roxb.) DC.) is a plant belonging to the Gentianaceae family that can be used as medicine for various diseases. This study aims to determine the pharmacological effectiveness of the Tembusu plant. The method used in this study is a literature review article (LRA) approach. The literature search used Pubmed, Google Scholar, Scient Direct and Research Gate as sources of electronic data published from 2010 to 2022. The results found 19 literatures that met the criteria. Based on a review of several literatures, it shows that the Tembusu plant has pharmacological activities including antimicrobial, antioxidant, anti-inflammatory, anticancer and antidiabetic activities.